Utilization of hepatitis B surface antigen-positive donors in liver transplantation for recipients with hepatocellular carcinoma: a retrospective and propensity score matching analysis - Chen,Zhitao; Ma,Yihao; Dong,Yuqi; Chen,Chuanbao; Wang,Hanyu; Wang,Tielong; Yu,Jia; Hong,Xitao; Chen,Maogen; He,Xiaoshun; Ju,Weiqiang (PeerJ, 2023)
Introduction The use of extended criteria donor (ECD) grafts such as donor with infection of hepatitis B virus (HBV) is a potential solution for organ shortage. In this study, we aimed to evaluate the safety and long-term survival of utilization of hepatitis B surface antigen-positive (HBsAg+) donor livers in HCC patients using propensity score matching (PSM) analysis. Methods Forty-eight donors with HBsAg-positive and 279 donors with HBsAg-negative were transplanted and enrolled in this study. PSM analysis were used to eliminate selection bias. Perioperative data and survival were collected and analyzed. Results PSM generated 44 patient pairs. When comparing intra- and post-operative data, no significant difference was found between groups (P > 0.05). Patients with a HBsAg-positive donor had significantly worse progression-free survival (1-year: 65.9% vs. 90.9%; 3-year: 18.1% vs. 70.4%, P = 0.0060) and overall survival (1-year: 84.1% and 95.4%; 3-year: 27.2% vs. 79.5%, P = 0.0039). In multivariate analysis, donor HBsAg-positivity was an independent risk factor for survival and occurrence (P = 0.005 and 0.025, respectively). Conclusion In conclusion, with adequate antiviral prophylaxis and treatment, utilization of HBsAg positive liver grafts did not increase the incidence of early-stage complications. However, patient with an HBsAg-positive graft had poorer progression-free survival and overall survival.
Keywords: Liver transplantation; Propensity score matching; Hepatitis B antigen-positive donor; Hepatocellular carcinoma; Progression-free survival; Overall survival